Analisis Penggunaan Bahasa Slang Pada Akun Twitter Jek dan Pemanfaatannya Sebagai Bahan Ajar Teks Observasi Siswa SMA - La'ali Luthfiyyah; Dewi Herlina Sugiarti; Sinta Rosalina (Peneliti.net, 2022)
This study aims to describe the form of the use of slang in the Twitter @Jek_ social media account. In this day and age, there are variations in language styles that are triggered by the development of increasingly rapid communication technology. This makes the style of language used by each group is different. So that the use of good and correct language is now starting to be shifted, namely the use of slang among teenagers. The problem in this study is the use of slang and changes in the meaning of slang in the March - July 2022 edition of Twitter social media account which aims to describe the form in the use of slang used on Jek's twitter account. comes from a tweet in the Twitter account @Jek_ March – July 2022 edition. This type of research is a qualitative descriptive study. The results of the study found that the use of slang forms of words included (1) basic words, (2) inventions, (3) acronyms, (4) abbreviations, (5) reduplications and (6) fragments. The slang vocabulary found not all of the vocabulary appears as new vocabulary, but some of this vocabulary is very popular among young Indonesians.